THE RELATION OF CLINICAL RESEARCH TO PRACTICE AND THE APPARENT CRISIS OF CONFIDENCE REVISITED - Grubb, Henry Jefferson (European Scientific Journal, ESJ, 2014)
Thirty years after Strupp and Barlow criticized the bifurcated and insular state of psychology, with researchers situated on one pole and clinicians at the opposite end of the applied-research spectrum, the profession finds itself little moved toward a merger of the two branches. It is agreed that Barlow’s appeal for the use of intensive local observation research will overcome all of the objections and reasons given by practicing psychologists for not being involved in research. Strupp’s assessment of the experimenter-clinician rift as a pseudo-problem is also addressed. Strupp’s conclusion that our training institutions are not properly teaching the skills needed by the clinician is extended. It is herein added that those being trained by our graduate schools are not simply being mis-trained or nontrained in appropriate research skills; we are possibly training the wrong future providers.